Metacognitive Awareness Inventory (MAI) Students in Online Learning - Dina Amalya Lapele (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2022)
This study is a descriptive qualitative study that aims to describe the Metacognitive Awareness Inventory (MAI) of online learning students. This study's sample size was 236 students. The sampling technique used is non-probability sampling of the convenience type. In this study, data is gathered through the use of a questionnaire. The data was analyzed by calculating the score and percentage of each statement item. The calculation data is then described per aspect and indicator to produce a representative conclusion. The findings revealed that students' metacognitive regulation was metacognitive knowledge in online learning